BIOKONSENTRASI DAN TRANSLOKASI LOGAM BERAT Cd PADA TANAMAN BAWANG MERAH DENGAN APLIKASI AMELIORAN - Cicik Oktasari Handayani; Triyani Dewi; Anik Hidayah (Departemen Tanah, Fakultas Pertanian, Universitas Brawijaya, 2018)
Onion is a strategic commodity with many benefits and high economic value. So the production and quality of onion quality must be improved, one of which is quality support is free from heavy metal content which can have direct effect to human health. One source of heavy metals in vegetables is obtained from fertilizer applications. This study aims to obtain information on bioaccumulation and translocation value of onion crops that have been given amelioran application. This research was conducted in shallot field at Igirklanceng Village, Sirampog Sub-district, Brebes Regency. The treatment is done in the field by utilizing biochar, compost, and biofertilizer. The results showed that the BCF> 1 score on the roots and stems of biochar treatment and biological fertilizer. TF value> 1 on stem in biochar treatment, biochar + biological fertilizer, biocompos + biological fertilizer, farmer treatment. BCF and TF values of tuber <1 in all treatments.